Silent cardiac abnormalities in medical ICU patients ( Egyptian experience) - Elham S. Said; Maggie B. Abadeer (SpringerOpen, 2013)
Background Patients hospitalized in medical ICUs (MICUs) with acute noncardiac illnesses may have underlying cardiovascular abnormalities, especially in Egypt where rheumatic heart disease is still frequently encountered. This may affect the diagnosis and/or plan of management. Routine cardiac examination may not be informative because of the acuteness of the illness and the need for frequent concurrent mechanical ventilation. PurposeThe purpose of this study was to utilize transthoracic echocardiography to define cardiac abnormalities, especially rheumatic valve disease that may be present in noncardiac patients. Materials and methodsOver a 4-month period, 75 patients without primary cardiac diagnoses admitted to the MICU of Kasr El Ainy hospital underwent transthoracic echocardiography (TTE). The MICU mortality rates and length of stay were compared in patients with and without significant cardiac abnormalities. Results One or more cardiac abnormalities were observed in 61.3% patients of the studied group. Of these abnormalities, 15% were rheumatic in origin. Right atrial and right ventricular dilatation were the most encountered lesions, followed by left ventricular hypertrophy and pulmonary hypertension. Although there was no correlation between the presence of cardiac abnormalities and the length of ICU stay or mortality, the plan of management was affected in 14.67% of patients. Conclusion A significant proportion of patients admitted to the MICU with noncardiac illness had underlying cardiac abnormalities, and this affected the plan of management in a significant number of patients.